Diseño de estrategias de desarrollo en el proyecto educativo pastoral salesiano a favor de los chicos de la calle - Mariño Robalino, Edwin Gonzalo (2005)
The present work aims to design development strategies involving different stakeholders involved in the Salesian Pastoral Education Project for Street Boys.